Batas Usia Perkawinan dalam Hukum Islam dan Hukum Negara: Studi Perbandingan Antara Indonesia dan Malaysia - Husnul Furqon; Sukiati Sukiati; Iwan Nasution (Lembaga Pengembangan Kinerja Dosen, 2026)
This study analyzes the minimum age of marriage in Islamic jurisprudence and compares it with the positive law regulations in Indonesia and Malaysia. Using a normative legal method with comparative and conceptual approaches, the study draws on primary sources, including the Qur'an, hadith, Law Number 16 of 2019 on Marriage in Indonesia, and the Islamic Family Law (Federal Territories) Act 1984 in Malaysia. The analysis focuses on how Islamic legal principles concerning marriage eligibility are interpreted and incorporated into contemporary legal frameworks in both countries. The findings reveal that Islamic jurisprudence (fiqh) associates marital readiness with the concept of baligh (puberty) without prescribing a specific numerical age, whereas state law establishes fixed minimum age requirements to safeguard the rights and welfare of women and children. Indonesia sets the minimum marriage age at 19 years for both males and females, while Malaysia prescribes 18 years for males and 16 years for females, with judicial dispensation available in both jurisdictions under certain circumstances. These legal arrangements demonstrate each country's effort to harmonize classical Islamic jurisprudence with contemporary social protection objectives through institutional ijtihad, reflecting a balance between religious principles, legal certainty, and public welfare in regulating marriage.